Efficacy and Safety of Androgen-Deprivation Therapy Combined with Docetaxel Plus Prednisone in High-Burden Metastatic Hormone-Sensitive Prostate Cancer - Hu L; Zhao Q; Bai H; Xie C; Shan X; Lu D; Chen Y; Han D; Xiao Z; Tian J; Wang D; Bi X; et al. (Cancer Management and Research, 2020)
Linjun Hu,1,* Qinxin Zhao,2,* Hongsong Bai,1 Chengming Xie,1 Xingli Shan,1 Dehu Lu,1 Yonghai Chen,1 Dongdong Han,1 Zejun Xiao,2 Jun Tian,2 Dong Wang,2 Xingang Bi,2 Nianzeng Xing2 1Department of Urology, Cancer Hospital of HuanXing Chaoyang District Beijing, Beijing, People’s Republic of China; 2Department of Urology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nianzeng XingDepartment of Urology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, No. 17, Panjiayuan South Li, Beijing, Chaoyang 100021, People’s Republic of ChinaEmail xingnianzeng@hotmail.comPurpose: The aim of this study was to evaluate the efficacy and safety of hormonal and synchronous docetaxel plus prednisone (DocP) in metastatic hormone-sensitive prostate cancer (mHSPC).Methods: One hundred fifty-one cases with high-burden mHSPC diagnosed at 1 single center from January 2014 to August 2018 were analyzed retrospectively. Among them, 85 cases received androgen-deprivation therapy (ADT) within 3 months, along with 6 cycles of docetaxel + prednisone (treatment group), whereas 66 received ADT alone (control group). The primary end point was the median overall survival (OS), while the secondary outcomes included prostate-specific antigen (PSA) progression-free survival (PFS), radiographic PFS, and the proportion of PSA falling to 0.2 ng/mL.Results: A total of 151 patients were included and followed up for a median of 34 months in this study. The median OS time in the treatment group was unavailable, but it was remarkably longer than that of the control group (P< 0.001). In addition, the PFS of PSA in the treatment group and control group was 17.9 months and 9.2 months, respectively (P< 0.001). Meanwhile, the radiographic PFS was 43 months in the treatment group and 19.8 months in the control group, respectively (P< 0.001). The proportions of PSA falling to 0.2 ng/mL were 53.7% and 23.3%, respectively (P< 0.001). However, there was no significant difference in the incidence of ≥ 3 toxic side effects between these 2 groups (P=0. 21).Conclusion: ADT combined with 6 cycles of docetaxel + prednisone chemotherapy benefits patients diagnosed with high-burden mHSPC in terms of the OS, PFS of PSA and radiographic, and the ratio of PSA falling to 0.2 ng/mL.Keywords: androgen-deprivation therapy; ADT, docetaxel, high-burden, metastatic hormone-sensitive, prostate cancer;PCa